2022
DOI: 10.51214/bocp.v4i2.195
|View full text |Cite
|
Sign up to set email alerts
|

Resiliensi dan Stres Kerja pada Karyawan yang Bekerja di Masa Pandemi Covid-19

Abstract: This study aims to determine the relationship between resilience and work stress on employees at PT.X who work during the covid-19 pandemic. Participants in this study were employees who served as supervisors at PT.X with a total population of 37 participants. The method used in this study is a quantitative approach, with a non-probability sampling technique, namely a saturated sampling technique by taking the entire population of 37 participants. Measurement of resilience uses the Connor-Davidson Resilience S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…This relationship shows a negative direction. The same research results were also revealed by Tampombebu and Wijono (2022), who showed that there was a negative relationship between resilience and work stress in employees working at PT. X during the COVID-19 pandemic.…”
Section: Introductionsupporting
confidence: 69%
“…This relationship shows a negative direction. The same research results were also revealed by Tampombebu and Wijono (2022), who showed that there was a negative relationship between resilience and work stress in employees working at PT. X during the COVID-19 pandemic.…”
Section: Introductionsupporting
confidence: 69%
“…The authors have suspected that these three variables simultaneously are good predictors of job stress. This conjecture is supported by several works of literature which have shown how these variables are related (Duong et al, 2020;Hayhurst et al, 2005;Kokoroko & 2019;Mittal & Bhakar, 2018;Posig & Kickul, 2004;Sirgy & Lee, 2018;Wallace, 2014;Tampombebu & Wijono, 2022). Even though, in reality, some of the KUPI members are women who already married and have children, their consistency in running the organization and profession can still be done well.…”
Section: Discussionmentioning
confidence: 73%
“…Stres di tempat kerja dipengaruhi oleh sejumlah keadaan; stres tidak berkembang dengan sendirinya. Menurut Robbins dalam Tampombebu & Wijono (2022) awal mula terjadinya stres dipengaruhi oleh beberapa elemen, termasuk faktor pribadi, organisasi, dan lingkungan. Tuntutan tugas, ekspektasi peran, tuntutan interpersonal, dan struktur organisasi merupakan beberapa karakteristik organisasi yang berdampak pada tingkat stres karyawan (Robbins, 2008dalam Tampombebu dan Wijono, 2022.…”
Section: Pendahuluanunclassified